Synergizing Financial Literacy, Lifestyle, and E-Wallet Use for Enhanced Saving Behavior: Memanfaatkan Financial Literacy, Lifestyle, dan Penggunaan E- Wallet untuk Meningkatkan Saving Behavior - Azzahra Prisichella; Sonja Andarini (Academia Open, 2025)
General Background: The rapid growth of digital technology has transformed financial systems worldwide, with students increasingly reliant on digital payment platforms such as e-wallets. Specific Background: While these innovations offer convenience, they may also encourage impulsive spending, raising concerns about students’ saving behavior. Knowledge Gap: Previous studies have shown inconsistent findings regarding the role of financial literacy, lifestyle, and digital payment use in shaping saving habits, highlighting the need for further investigation. Aims: This study examines the influence of financial literacy, lifestyle, and e-wallet usage on students’ saving behavior at Universitas Pembangunan Nasional “Veteran” Jawa Timur. Results: Using survey data from 300 respondents and SmartPLS analysis, the findings reveal that financial literacy, lifestyle, and e-wallet usage each have a positive and significant effect on saving behavior, with financial literacy contributing the strongest influence. Collectively, these variables explain 45.8% of the variation in saving behavior. Novelty: This study uniquely demonstrates that when managed wisely, lifestyle choices and digital financial tools, often seen as consumption drivers, can in fact reinforce positive financial habits. Implications: The findings underscore the importance of strengthening financial literacy education and promoting mindful technology use as strategic approaches to foster sustainable financial resilience among students. Highlights: Financial literacy has the strongest influence on saving behavior. Lifestyle management supports positive saving habits. E-wallets can aid saving when used wisely. Keywords: Financial Literacy, Lifestyle, E-Wallet, Saving Behavior, Students